Mixed Mycobacterium tuberculosis Lineage Infection in 2 Elephants, Nepal - Paudel, Sarad (Emerg Infect Dis, 2019)
Tuberculosis in elephants is primarily caused by Mycobacterium tuberculosis. We identified mixed M. tuberculosis lineage infection in 2 captive elephants in Nepal by using spoligotyping and large sequence polymorphism. One elephant was infected with Indo-Oceanic and East African–Indian (CAS-Delhi) lineages; the other was infected with Indo-Oceanic and East Asian (Beijing) lineages.